Profile of notified tuberculosis cases and factors associated with treatment dropout - Paixão, Lúcia Miana M.; Gontijo, Eliane Dias (Revista de Saúde Pública, 2007)
OBJECTIVE: To describe the profile of notified tuberculosis cases and analyze the factors associated with treatment dropout. METHODS: A total of 178 cases of tuberculosis notified in the western region of Belo Horizonte (Southeastern Brazil) in 2001 and 2002 and recorded in the National System for Notifiable Diseases were described. An unmatched case-control study was conducted, with data collected by means of interviews, to compare patients who dropped out of treatment with those who achieved cure. The following variables were analyzed: sociodemographic and behavioral characteristics, associations with AIDS, side effects, information on the disease and interest in treatment. Univariate analysis and unconditional logistic regression for multivariate analysis were used. Adjusted odds ratios with 95% confidence limits were used as the measurement for associations. RESULTS: The coefficient of incidence was 56.6/100,000 inhabitants. There was predominance of men aged 30 to 49 years and of the pulmonary form (76.4%) and bacillary form (72.5%). Among the notified cases, 65.2% achieved cure, 12.4% dropped out of treatment and 9.6% died. Treatment location had no influence on the results. In the case-control study, there was no difference regarding gender, color, schooling, income, occupation, family support, association with AIDS and alcohol consumption. The use of drugs, interest in treatment and information about the disease were shown to be independently associated with dropout. CONCLUSIONS: Adherence to treatment is a challenge in controlling tuberculosis. The protection factors (interest in treatment and information about the disease) and recognition that drug use is a risk factor must form part of the strategies for patient care in order to reduce dropout rates and restore health.